The Impact of Original Programming and Product Quality on Brand Trust and Brand Loyalty - Sirait, Kezhia Bianta (Al-Qalam Institue, 2025)
The development of digital technology has changed people's entertainment consumption patterns, including the shift from conventional television to streaming services. This study aims to examine the effect of original programming and product quality on brand loyalty, with brand trust as a mediating variable. This study used a quantitative approach through a survey of 95 respondents with a purposive sampling technique. Data were analyzed using linear regression, path analysis, and the Sobel mediation test. The results show that original programming and product quality have a positive and significant effect on brand trust and brand loyalty with an Adjusted R square value of 0.941. In addition, brand trust is proven to significantly mediate the relationship between the two independent variables and brand loyalty. This research highlights the need for managers in the digital entertainment industry to focus on enhancing original programming and maintaining high product quality to foster brand trust. Strengthening brand trust can lead to increased brand loyalty, offering a competitive advantage in a rapidly evolving market. The findings suggest that companies should invest in content creation and quality improvements as strategies to build and sustain long-term customer loyalty.